2020
DOI: 10.1021/jacs.0c07357
|View full text |Cite
|
Sign up to set email alerts
|

Difunctionalization of C–C σ-Bonds Enabled by the Reaction of Bicyclo[1.1.0]butyl Boronate Complexes with Electrophiles: Reaction Development, Scope, and Stereochemical Origins

Abstract: Difunctionalization reactions of C−C -bonds have the potential to streamline access to molecules that would otherwise be difficult to prepare. However, the development of such reactions is challenging because C−C -bonds are typically unreactive.Exploiting the high ring-strain energy of polycyclic carbocycles is a common strategy to weaken and facilitate the reaction of C−C -bonds, but there are limited examples of highly strained C−C -bonds being used in difunctionalization reactions. We demonstrate that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 112 publications
(61 reference statements)
0
30
0
Order By: Relevance
“…Aggarwal and co-workers, building on their related work with in situ generated BCB boronate complexes, 76,77 demonstrated that these boronates can be efficiently attacked by electrophilic radicals. Indeed, BCB-containing boronate complexes undergo triuoromethylation via bridgehead bond homolysis upon irradiation with blue LED light (Scheme 7D).…”
Section: Homolytic Strain-release Functionalizationmentioning
confidence: 99%
“…Aggarwal and co-workers, building on their related work with in situ generated BCB boronate complexes, 76,77 demonstrated that these boronates can be efficiently attacked by electrophilic radicals. Indeed, BCB-containing boronate complexes undergo triuoromethylation via bridgehead bond homolysis upon irradiation with blue LED light (Scheme 7D).…”
Section: Homolytic Strain-release Functionalizationmentioning
confidence: 99%
“…resulted in similar transformations and allowed the modular construction of bifunctional diastereomerically enriched cyclobutanes (Scheme 81 B). [338] Moreover, radical addition to the central σ-bond of bicyclo [1.1.0]butane derivative 291 was developed. [339] Thus, electrondeficient radicals derived from the corresponding alkyl iodides under visible light irradiation can add to 291 1,3-dialkylsubstituted cyclobutyl boronates with high efficiency and stereocontrol (Scheme 81 C).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…In 2020, Aggarwal and coworkers reported a more general protocol for the 1,2-metallate rearrangement of bicyclo[1.1.0]butylboronic ester ate-complex (Scheme 10). 31 The authors revealed that the ate-complex was reactive toward a broad range of electrophiles to trigger 1,2-metallate rearrangement. In addition to a halogenating agent (bromonium, chloronium), which are well known to trigger the metallate rearrangement of vinylboronic ester ate-complex, carbonyl compounds (aldehyde, ketone, imine, acid chloride, chloroformate, and CO 2 ) could also be successfully used as an electrophile to afford the corresponding 1,3-dialkyl substituted cyclobutylboronic esters in good yield with high cis-selectivity (6367).…”
Section: Bicyclo[110]butanementioning
confidence: 99%